2016
DOI: 10.1016/j.funbio.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification, and characterization of a novel cold-active superoxide dismutase from the Antarctic strain Aspergillus glaucus 363

Abstract: The Antarctic fungal strain Aspergillus glaucus 363 produces cold-active (CA) Cu/Zn-superoxide dismutase (SOD). The strain contains at least one gene encoding Cu/Zn-SOD that exhibited high homology with the corresponding gene of other Aspergillus species. To our knowledge, this is the first nucleotide sequence of a CA Cu/Zn-SOD gene in fungi. An effective laboratory technology for A. glaucus SOD production in 3 L bioreactors was developed on the basis of transient cold-shock treatment. The temperature downshif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…High concentrations of superoxide dismutase were produced by the Antarctic fungus Aspergillus glaucus 363 following cold stress at 10.0 C using a nitro-blue tetrazolium substrate [84]. Tosi et al [126] reported catalase production by fungal strains recovered from soil samples belonging to the genera Aspergillus, Cladosporium, and Penicillium.…”
Section: Superoxide Dismutases and Catalasesmentioning
confidence: 99%
See 2 more Smart Citations
“…High concentrations of superoxide dismutase were produced by the Antarctic fungus Aspergillus glaucus 363 following cold stress at 10.0 C using a nitro-blue tetrazolium substrate [84]. Tosi et al [126] reported catalase production by fungal strains recovered from soil samples belonging to the genera Aspergillus, Cladosporium, and Penicillium.…”
Section: Superoxide Dismutases and Catalasesmentioning
confidence: 99%
“…Cold-adapted antioxidant enzymes, such as superoxide dismutases and catalases can be very important for the prevention of skin injury when used in cosmetic formulations. These enzymes can also be used in medicine, as a pulp-capping agent, as an inhibitor of pulmonary vascular oxidative stress, and in the treatment of septic shock [84,126].…”
Section: Superoxide Dismutases and Catalasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni‐SOD is relatively little research, and only found in Streptomyces and cyanobacteria . SODs, as superoxide anion radical scavengers, have been widely applied in the medical, agricultural, food, and cosmetics industry .…”
Section: Introductionmentioning
confidence: 99%
“…Raychaudhuri et al firstly reported the presence of cytosolic Fe‐SOD in yeast Rhodotorula glutinis . Untill now, Fe‐SOD genes had been detected in several yeasts and fungi, such as Rhodosporidium toruloides CECT1137 , Rhodotorula toruloides NP11 , Aspergillus glaucus 363 .…”
Section: Introductionmentioning
confidence: 99%